Meningkatkan Kecakapan Hidup Masa Pandemi Covid-19 Melalui Kegiatan Ekstrakurikuler Tilawati - Syaiful Rizal (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2022)
Abstract : Life skills are abilities, abilities and skills needed by a person to maintain his survival and self-development. Learning life skills during the pandemic that is carried out from home online requires good cooperation between the school/madrasah and the parents of students. Tilawati extracurricular activities cannot be carried out online. Therefore, to find alternative ways to manage life skills learning during a pandemic, the learning is done from home online. The formulation of the problem in this study is how the teacher's efforts in improving general and specific life skills through Tilawati Group A extracurricular activities in Raudhatul Athfal Baiturrahman, Arjasa District, Jember Regency. The research method uses a qualitative approach. The results of the study indicate that the Teacher's Efforts in Improving General Life Skills include Personal Skills and Social Skills. While the Teacher's Efforts in Improving Specific Life Skills include Academic Life Skills and Vocational Life Skills.